The Integration of Fuzzy Analytic Hierarchy Process and VIKOR for Supplier Selection - Ahmad, Nazihah binti; Mat Kasim, Maznah; Ibrahim, Hawa (International Journal of Supply Chain Management, 2017)
Supplier selection is one of the Multi-Criteria Decision Making problems since it involves many suppliers with different criteria that often conflict with each other. This paper shows the integration of Fuzzy Analytical Hierarchy Process (FAHP) and VIKOR methods in selecting the best supplier in a selected automotive spare part manufacturing company.  FAHP is used to calculate the important weights of the evaluation criteria and the overall performance for ranking of suppliers is then determined by VIKOR. Results show that there is no supplier with the same performance value from the FAHP-VIKOR analysis as compared to normal practice in that particular company which eventually can help the decision maker to select the supplier.